2017
DOI: 10.1159/000457812
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Blood Pressure Measurement in Maintenance Hemodialysis Patients: Comparison of Agreement between Oscillometric and Finger-Cuff Methods

Abstract: Background: The Nexfin monitor is a device used for measuring arterial blood pressure (BP) continuously and noninvasively through finger-cuff technology. Since it was validated against the auscultatory method using a sphygmomanometer, the aim of this study was to test the ability of the Nexfin to evaluate brachial arterial pressure (BAP) in maintenance hemodialysis patients, quantifying accuracy and precision. Methods: Forty hemodynamically stable hemodialysis patients underwent serial measurements of Nexfix a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The authors suggested that the reason for the poor results of the Nexfin system might be related to the high prevalence of vasculopathy in their patient cohort with a mean age of 68.9 years. 13 In accordance to our study, best results were shown for MAP and SAP while performance for DAP again was worst. The diastole marks the lowest part of the arterial curve between two heartbeats.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The authors suggested that the reason for the poor results of the Nexfin system might be related to the high prevalence of vasculopathy in their patient cohort with a mean age of 68.9 years. 13 In accordance to our study, best results were shown for MAP and SAP while performance for DAP again was worst. The diastole marks the lowest part of the arterial curve between two heartbeats.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies also described a rather poor performance of the Nexfin device and pulse contour analysis techniques during hypotension. 18,19,38 In a prospective study by Alfano et al, 13 the vascular unloading technique did not correspond to oscillometric blood pressure recordings in 40 hemodynamically stable patients requiring hemodialysis. The authors suggested that the reason for the poor results of the Nexfin system might be related to the high prevalence of vasculopathy in their patient cohort with a mean age of 68.9 years.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…According to the Association for the Advancement of Medical Instrumentation (AAMI), product standard uses the mean difference in BP measurements between these devices and “gold standard” measurements should be <5 mmHg, with a standard deviation <8 mmHg ( 3 ). Alfano et al compared finger-cuff with a conventional oscillometric method in 40 hemodynamically stable hemodialysis patients ( 14 ) and found that the measured values were significantly different between the two methods. This study included an elderly population (65% of whom were over 65 years of age), where vascular calcifications are recognized in up to 88% of the patients.…”
Section: Monitoring Technologymentioning
confidence: 99%
“…The software captures the average color of multiple regions of interest 30 times every second for 60 seconds; subtle changes in coloration are used to determine VSs (Figure 1). [15][16][17] Weighted average of performance of 3 devices 2.2 (9.2) Pulse rate (beats per minute) [15,16,18,19] Weighted average of performance of 4 devices 2.3 (5.0) Respiratory rate (respirations per minute) Finger photoplethysmography monitor [20][21][22][23][24][25] Weighted average of performance of 6 devices 6.7 (15.3) Systolic blood pressure (mmHg) [20][21][22][23][24][25] Weighted average of performance of 6 devices 5.5 (8.9) Diastolic blood pressure (mmHg) a Relevance and quality scores: 3.0-3.16 for pulse rate, 2.83-3.16 for respiratory rate, 2.83-3.5 for systolic/diastolic blood pressure. Here, we report early validation steps of the Lifelight software for the measurement of PR, RR, SBP, and diastolic BP (DBP; in line with the intended purpose of Lifelight) [26].…”
Section: Introductionmentioning
confidence: 99%